KINEMATIC AND DYNAMIC ANALYSIS OF MARKING MECHANISM OF ONE STEEL PLATE MARKING MACHINE - FU Min; LIN LiFeng (Jixie qiangdu)
The marking mechanism,as an important part of one steel plate marking machine that before heat treatment,its dynamic characteristic could influence marking effect.First,estiblished 3D model of marking mechanism by Pro/E,using the condition of marking typical character "N " as example,kinematics analysis have been done,obtain the law of speed and acceleration varies with time when marking character;on the basis of it,build the finite element model of marking mechanism according to actual condition and transient dynamics analysis has been completed based on Ansys Workbench,solved the curve of maximium stress and deformation varies with time,the result shows that the intensity and stiffness of marking mechanism could satisfy the requirement,and provide theory foundation for the structure design and optimization.